Bi-allelic loss-of-function variants in BCAS3 cause a syndromic neurodevelopmental disorder. - Hengel, H.; Hannan, S.B.; Dyack, S.; MacKay, S.B.; Schatz, U.; Fleger, M.; Kurringer, A.; Balousha, G.; Ghanim, Z.; Alkuraya, F.S.; Alzaidan, H.; Alsaif, H.S.; et al. (American Journal of Human Genetics, 2021)
BCAS3 microtubule-associated cell migration factor (BCAS3) is a large, highly conserved cytoskeletal protein previously proposed to be critical in angiogenesis and implicated in human embryogenesis and tumorigenesis. Here, we established BCAS3 loss-of-function variants as causative for a neurodevelopmental disorder. We report 15 individuals from eight unrelated families with germline bi-allelic loss-of-function variants in BCAS3. All probands share a global developmental delay accompanied by pyramidal tract involvement, microcephaly, short stature, strabismus, dysmorphic facial features, and seizures. The human phenotype is less severe compared with the Bcas3 knockout mouse model and cannot be explained by angiogenic defects alone. Consistent with being loss-of-function alleles, we observed absence of BCAS3 in probands' primary fibroblasts. By comparing the transcriptomic and proteomic data based on probands' fibroblasts with those of the knockout mouse model, we identified similar dysregulated pathways resulting from over-representation analysis, while the dysregulation of some proposed key interactors could not be confirmed. Together with the results from a tissue-specific Drosophila loss-of-function model, we demonstrate a vital role for BCAS3 in neural tissue development.